Some approaches in organizing the activities of the practical psychologist in special conditions - Sereda Юлия (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2014)
The article discusses one of the methods of psychological assistance – psychological debriefing. This method creates a special way-organized discussion and minimizes the psychological suffering of both rescue workers and the affected population of the country, which will keep the mental, emotional and physical well being.